RESTORATIVE JUSTICE DALAM PERKARA PIDANA PENGANIAYAAN DI KEPOLISIAN RESOR KOTA SIDOARJO - E. Akbar Alibasah; Dossy Iskandar Prasetyo (Fakultas Hukum Universitas Bhayangkara Surabaya, 2025)
This research examine the application of the restorative justice approach in cases of assault within the jurisdiction of the Sidoarjo City Police. Assault not only causes physical harm but also significant psychological trauma for victims. However, the Indonesian criminal justice system tends to focus on punishing perpetrators and does not sufficiently prioritize victim recovery and social reconciliation. This study aims to analyze the role of the police in promoting the application of restorative justice and its impact on the restoration of the rights of assault victims. The research method used is an empirical legal approach with qualitative methods through literature review and interviews with Sidoarjo City Police investigators, victims, and offenders. The results of the study indicate that the Sidoarjo City Police implement restorative justice in cases of minor assault through a mediation process facilitated by investigators to reach a peaceful settlement. This approach has a positive impact on the psychological recovery of victims because victims are given a space to be heard and to be actively involved in the case resolution process. This study concludes that restorative justice is an important innovation in criminal justice system reform that requires support from stronger regulations as well as capacity building for law enforcement officials.